Research status and trends of soil pollution from 1999 to 2018. Issue 3 (March 2021) - Dan, Wu
Abstract: In order to understand the global research status and development trend in the field of soil pollution remediation, this paper, based on the Web of Science (WOS) database, conducted a statistical analysis of the SCI papers in this field from 1999 to 2018 through bibliometric method, and quantitatively explored the development and change trend of the topic in this field.It was found that the number of papers published in the field of soil remediation in the world showed a linear growth trend with each year, while the number of papers published in China showed an exponential growth trend with each year, indicating that China pays more and more attention to this field.